2021
DOI: 10.21203/rs.3.rs-345791/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SUMOylation Regulates TDP-43 Splicing Activity and Nucleocytoplasmic Distribution

Abstract: The nuclear RNA-binding protein TDP-43 forms abnormal cytoplasmic aggregates in the brains of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) patients and several molecular mechanisms promoting TDP-43 cytoplasmic mislocalization and aggregation have been proposed, including defects in nucleocytoplasmic transport, stress granules (SG) disassembly and post-translational modifications (PTM). SUMOylation is a PTM which regulates a variety of cellular processes and, similarly to ubiquitination… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Although site-directed mutagenesis is a powerful tool to stimulate small post-translational modifications of amino acids such as serine/threonine phosphorylation and lysine acetylation, respectively, the aspartate/glutamate and glutamine substitutions are not identical to the phosphorylated or acetylated residues. Although molecular dynamics simulations suggested little impact of the K136R substitution on the local structure within the RNA-binding domain [166], subtle clashes with bound RNA cannot be ruled out [125]. Nevertheless, amber suppression confirmed the results of site-directed mutagenesis, showing that K136 acetylation reduced RNA binding and splicing activity.…”
Section: Tdp-43 Lysine Acetylationsmentioning
confidence: 69%
See 2 more Smart Citations
“…Although site-directed mutagenesis is a powerful tool to stimulate small post-translational modifications of amino acids such as serine/threonine phosphorylation and lysine acetylation, respectively, the aspartate/glutamate and glutamine substitutions are not identical to the phosphorylated or acetylated residues. Although molecular dynamics simulations suggested little impact of the K136R substitution on the local structure within the RNA-binding domain [166], subtle clashes with bound RNA cannot be ruled out [125]. Nevertheless, amber suppression confirmed the results of site-directed mutagenesis, showing that K136 acetylation reduced RNA binding and splicing activity.…”
Section: Tdp-43 Lysine Acetylationsmentioning
confidence: 69%
“…As for de-ubiquitinating enzymes, only the rather general UBPY/USP8 has been described so far, counteracting ubiquitinylated TDP-43 pathology in cell and fly models [44]. TDP-43 is also a target for the small ubiquitin-related modifier (SUMO ) [165,166]. A SUMOylation consensus site comprises K136 within the RNA binding domain.…”
Section: Tdp-43 Ubiquitin Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our study showed that the SUMOylation of FgSR controls DDR gene transcription not only by modulating its occupancy on target gene promoter resulting from nuclear‐cytoplasmic partitioning but also by regulating pre‐mRNA splicing, which provides a novel insight into the functions of SUMOylation of transcription factors. Previous studies have reported that SUMOylation is involved in pre‐mRNA splicing mainly via modifying splicing‐related proteins (Liu et al ., 2015; Pozzi et al ., 2017, 2018; Maraschi et al ., 2021). To our knowledge, this is the first report of SUMO modification of transcription factors participates in pre‐mRNA splicing regulation.…”
Section: Discussionmentioning
confidence: 99%